(untitled) (Semiárida, 2020)
Three segregated generations (F2, F3 Y F4) of tricepiros originated from the crosses between triticale Don Santiago INTA and trigopiro Don Noé INTA were analyzed. The characteristics evaluated were: plant height. cycle to flowering. fertile tillers. ear length. grains by ear, grains by spikelet (fertility). weight of 1000 grains and harvest index Triticale was taken Iike reference in the analysis of the variability at each generation. The plant cycle to flowering in the generations F3 and F4. was longer than triticale but the plant height. was smaller. Positive and significant associations between harvest index and grain per spike were found. In the three generation analyzed the weight of 1000 grains were associated positive and significant with grain by ear and plant height whith spikelet by ear. The low hereditary transmission perhaps were caused by the persistence of a chromosomic and genic segregation. Analyzed the effect of the selection of superior 10% of families F3 with respect to the following generation. the plant height would be a favorable characteristic to increase the grain yield by plant since it increases the components of yield: fertile tillers (ears). grains by ear and to some extent the weight of 1000 grains.